Development of Short Circuits for Agroecology: Case of the Madre Tierra Solidarity Market in Quito, Ecuador - Pazmiño-Guevara, Lizzie; Álvarez-Tello, Jorge; Becerra-Sarmiento, María; Guerrero-Vargas, Roberto (Springer Link, 2024)
Introduction: The study evaluates the potential for responsible consumption of agroecological products in Madre Tierra fairs, in the D.M. of Quito-Ecuador, its impact on food security and the recognition of agroecological products in the region. Objective: To evaluate the promotion of responsible consumption and the adoption of business models that integrate technology and digital marketing strategies. Method: A descriptive qualitative-quantitative approach is used, through participatory research that evaluated the profile of the agroecological food consumer. An ecosystem is built with actors that contribute to the strategies and strengthen characteristics of a resilient environment for the improvement of accessibility to agroecological products. Results: The study shows that final consumers, who source their food from agroecological fairs, play a crucial role in their diet. Most consumers are women (62%), are between 31 and 50 years old and spend an average of 20 USD in family units of 4 people. In addition, 60% of the respondents are not aware of toxic-free foods and only 22% consume adequately. The surveys were conducted in four different locations in La Mena. Conclusion: Finally, the Madre Tierra fairs promoted responsible consumption through consumer characterization, training, new business models for associative enterprises and digital marketing strategies. In addition, the integration of stakeholder information and the improvement of responsible consumption through social construction projects were promoted.
Keywords: Madre Tierra Solidarity Market; Quito; Ecuador; agroecology; short circuits